Arctic summary report. - Outer Continental Shelf Oil and Gas Information Program (U.S.); United States. Minerals Management Service (Reston, Va. : U.S. Dept. of the Interior, Minerals Management Service, 1985)
Description based on: 1983. Updates published irregularly between eds. "Outer continental shelf oil and gas activities in the Arctic and their onshore impacts." Mode of access: Internet. Vols. for -Jan. 1985 prepared for the Outer Continental Shelf Oil and Gas Information Program. Merged with: Bering Sea summary report, and: Gulf of Alaska summary report, to form: Alaska summary report.